Covalently Connected Polymer–Protein Nanostructures Fabricated by a Reactive Self‐Assembly Approach. Issue 14 (7th February 2017) - Ju, Yuanyuan; Xing, Cheng; Wu, Dongxia; Wu, Yunfang; Wang, Lianyong; Zhao, Hanying
Abstract: The synthesis of polymer–protein nanostructures opens up a new avenue for the development of new biomaterials. In this research, covalently connected polymer–protein nanostructures were fabricated through a reactive self‐assembly approach. Poly( tert ‐butyl methacrylate‐ co ‐pyridyl disulfide methacrylamide) (P t BMA‐ co ‐PPDSMA) was synthesized by reversible addition fragmentation chain transfer (RAFT) polymerization. Covalently connected nanostructures (CCNs) with hydrophobic polymer cores and hydrophilic protein coronae were prepared by adding solutions of P t BMA‐ co ‐PPDSMA/DMF to aqueous solutions of bovine serum albumin (BSA). The thiol–disulfide exchange reaction between pyridyl disulfide groups on the polymer chains and thiol groups on the protein molecules plays a key role in the fabrication of CCNs. The self‐assembly process was investigated by dynamic light scattering (DLS) and stopped‐flow techniques. DLS results indicated that the sizes of the CCNs were determined by the initial polymer concentration, the BSA concentration, and the average number of thiol groups on BSA molecules. TEM and sodium dodecyl sulfate polyacrylamide gel electrophoresis were used to analyze the nanostructures. Far‐UV circular dichroism results demonstrated that the original folded conformations of BSA molecules were basically maintained in the reactive self‐assembly process. Compared with native BSA, the secondary structure and conformation change of coronal BSA induced by urea or thermal treatment were remarkably suppressed. The cytotoxicity assays demonstrated that the CCNs were essentially nontoxic to Hela and COS‐7 cells. Abstract : Creating coronae : Covalently connected nanostructures with polymer cores and protein coronae are prepared by a reactive self‐assembly approach (see figure). The in situ thiol–disulfide exchange reaction between a polymer containing pyridyl disulfide groups (poly( tert ‐butyl methacrylate‐ co ‐pyridyl disulfide methacrylamide) (P t BMA‐ co ‐PPDSMA)) and bovine serum albumin (BSA) molecules plays a key role in the self‐assembly process.